Peptide Aptamer PA3 Attenuates the Viability of Aeromonas veronii by Hindering of Small Protein B-Outer Membrane Protein A Signal Pathway - Liu, Peng; Chang, Huimin; Xu, Qi; Wang, Dan; Tang, Yanqiong; Hu, Xinwen; Lin, Min; Liu, Zhu (Frontiers in Microbiology, 2022)
Small protein B (SmpB), previously acting as a ribosome rescue factor for translation quality control, is required for cell viability in bacteria. Here our study reveals that SmpB possesses new function which regulates the expression of outer membrane protein A (ompA) gene as a transcription factor in Aeromonas veronii. The deletion of SmpB caused the lower transcription expression of ompA by qPCR. EMSA and DNase I Footprinting verified that SmpB bound at the regions of -46 -28 bp, -18 +4 bp, +21 +31 bp, and +48 +59 bp of the predicted ompA promoter (PompA). The key sites C52AT was further identified to interact with SmpB when PompA was fused with EGFP and co-transformed with SmpB expression vector for fluorescence detection, and the result was further confirmed in microscale thermophoresis (MST) assays. Besides, the amino acid sites G11S, F26I and K152 in SmpB were the key sites for binding to PompA. In order to further develop peptide antimicrobial agents, the peptide aptamer PA3 was screened from the peptide aptamer library by bacterial two-hybrid method. The drug sensitivity test showed that PA3 effectively inhibited the growth of A. veronii. In summary, these results demonstrated that OmpA was a good drug target for A. veronii, which was regulated by SmpB protein. And the selected peptide aptamer PA3 interacted with OmpA protein to disable SmpB/OmpA signal pathway and inhibit A. veronii, suggesting that it could be used as an antimicrobial agent for the prevention and treatment of pathogens.